Static output feedback controller design for uncertain polynomial systems: an iterative sums of squares approach - Md Saat, Mohd Shakir (The Institution of Engineering and Technology, 2011)
This study examines the problem of designing a static output feedback controller for uncertain polynomial systems via an iterative sums of squares (SOS) approach. The derivation of the static output feedback controller is given in terms of the solvability conditions of state-dependent bilinear matrix inequalities (BMIs). An iterative algorithm based on the SOS decomposition is proposed to solve these state-dependent BMIs. Finally, numerical examples are provided at the end of the study as to demonstrate the validity of the proposed design technique.